THE APPLICATION OF KGRE PROCEDURE IN TEACHING LISTENING TO THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 9 PALEMBANG - Andika Andika; Vivin Afini (Universitas PGRI Palembang, 2023)
The main problem of this study was formulated as follows: â€œWas it effective to teach listening comprehension by applying KGRE Procedure to eleventh grade students of SMA Negeri 9 Palembang?â€ The main objective of this study is to find out whether or not KGRE Procedure was effective to apply in teaching listening comprehension to the eleventh grade students of SMA Negeri 9 Palembang. This study used the true experimental method. The population of this study was 184 students and the sample was 70 students taken by using cluster random sampling. The two hypotheses used were: (1) The null hypothesis (Ho), and (2) the alternative hypothesis (Ha). The data were collected by a completion test. The result of test was analyzed by means of matched t-test formula. Based on the result data analyzed, there were two major findings: (1) the data obtained form the post-test, and (2) the result of data analyzed by means of the matched t-test formula. The studentsâ€™ average score of post-test in the control group was 7.27. After analyzing the studentsâ€™ t-obtained, it was found out that the obtained â€œtâ€ was 5.04. Thus, the score was higher than the critical value of t-table (1.699). based on the explanation before, it showed that the null hypothesis was rejected and alternative hypothesis was accepted. It means that it was effective to teach listening by applying KGRE Procedure a SMA Negeri 9 Palembang.